Exploitation and Marginalization of Women in Online Media News - Putri, Dian Marisha; Marsella, Emma (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The phenomenon of online media coverage is that many women's reports exploit the existence of women as objects to seek benefits from this gender, the news of the two women who are used as objects that are treated as biological satisfiers, as objects that can be harassed or even marginalized. The primary data of the study were 10 online media reports, using Nourman Fairclough's Critical Discourse Analysis tool about "Exploitation and Marginalization of Women in Online Media Reporting". This qualitative descriptive research method aims to describe: (1) Marginalizing women's news in online media.Based on the results of data analysis, it can be concluded that eThe exploitation of women in online media includes: a) Online prostitution, b) Women are made into commodities, c) Threats of digital violence, d) Women are sexually harassed, e) Harassment of women in the name of local culture, f) Contract marriage 'siri' marriage. Whereas the form 2) Marginalizing Women in Online Media is carried out such as: a) Title of online news that corner women, b) Marginalizing women by using diction, c) Lowering the dignity of women with culture, d) Lowering the dignity of women with terms.